Strand-specific RNA-sequencing analysis of multiple system atrophy brain transcriptome. (13th May 2016) - Mills, J.D.; Ward, M.; Kim, W.S.; Halliday, G.M.; Janitz, M.
Highlights: The first strand-specific RNA-sequencing study of multiple system atrophy. Evidence of widespread antisense transcription in the frontal cortex. Over 50% of the differentially expressed genes are putative lincRNAs. Metabolism and immune response genes are altered in the multiple system atrophy. Abstract: Multiple system atrophy (MSA) is a sporadic neurodegenerative disease. The major pathological hallmark of MSA is the accumulation of α-synuclein in oligodendrocytes. In contrast to Parkinson's disease no definitive familial etiology for MSA has been determined. Yet, there is a growing body of evidence that perturbation of transcriptional processes leads to MSA pathology. Here we present the results of the first ribosomal-depleted strand-specific RNA-sequencing profile of the MSA brain frontal cortex tissue. Among the 123 differentially expressed genes over 50% were categorized as putative long intervening non-coding RNAs (lincRNAs). Along with the dysregulation of the non-coding portion of the transcriptome, the expression of protein coding genes was also affected, including serpin peptidase inhibitor, clade A (alpha-1 antiproteinase, antitrypsin), member 3 ( SERPINA3 ), interleukin 1 receptor-like 1 ( IL1RL1 ) and hemoglobin, beta ( HBB ). Also of interest was the alternative splicing of SNCA, along with the presence of an antisense transcript overlapping the 3′ exon of SNCA . Moreover, we demonstrate widespread antisense transcription throughout the frontal cortex that is largely not affected by MSA-specific neurodegenerative process. MSA causes a large disruption of lincRNAs in the human brain along with protein coding genes related to iron metabolism and immune response regulation. Most of the lincRNAs specific for MSA were novel. Hence our study uncovers another level of complexity in transcriptional pathology of MSA.